Efek Antiplasmodium dari Ekstrak Etilasetat Kulit Batang Asam Kandis (Garcinia parvifolia) secara In Vitro - Syamsudin Syamsudin; Budi Prasetyo; Antonius Antonius (Fakultas Farmasi Universitas Pancasila, 2007)
This research was carried out to assess the antiplasmodic activity of six fractions from the aethylacetate extract of the stem barks of Garcinia parfivolia. The result showed that fractions C, D, and G were IC50 < 10 µg/ml, fraction E: IC50 24,19 µg/ml, and fraction F and H: > 100 µg/ml against a chloroquine resistant strain of P. falciparum FCR-3.